2019
DOI: 10.1093/eurpub/ckz186.415
|View full text |Cite
|
Sign up to set email alerts
|

Employment program graduates of internship of higher education institutions of Kazakhstan

Abstract: Background Employment of graduates of medical universities is one of the traditional problems of health care in the Republic of Kazakhstan (RK). The annual graduation of medical universities of RK exceeds 4500 young specialists. Despite this, as well as the positive dynamics of employment, the health care industry continues to experience a shortage of medical personnel. Methods To take effective measures to improve the employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Literature [11] builds a vocational education BD technology training platform based on IPE, which provides a solution for the development of information technology in the integration of Industry and education and can adaptively adjust the content of the webpage to provide personalized services. Literature [12] aims to improve the employment performance of graduates of medical education institutions and to compensate for the shortage of medical personnel. An electronic platform with a complete database of students and graduates was created, with functions such as monitoring employment, tracking the trajectory of graduates, and organizing university employment services.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [11] builds a vocational education BD technology training platform based on IPE, which provides a solution for the development of information technology in the integration of Industry and education and can adaptively adjust the content of the webpage to provide personalized services. Literature [12] aims to improve the employment performance of graduates of medical education institutions and to compensate for the shortage of medical personnel. An electronic platform with a complete database of students and graduates was created, with functions such as monitoring employment, tracking the trajectory of graduates, and organizing university employment services.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [12], based on entropy theory and fuzzy comprehensive evaluation method, designed a postgraduate graduation employment quality assessment framework, which helps to optimize the way of talent cultivation and promotes the improvement of the employment quality level of graduated talents. Literature [13] reveals that the proportion of graduated medical talents in Kazakhstan is less than 50%, which is unable to meet the shortage of medical talents, and proposes to build a platform for tracking the employment of graduated medical graduates and improve the auxiliary services for employment support. Literature [14] investigated the employment intention of international dental students and found that the proportion of international dental graduates who stayed back to New Zealand for employment has gradually declined since 2001, which provides some information reference for the talent management department of the home country.…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee a certain employment rate, the career guidance course for college students plays a role that cannot be underestimated [5]. Although the career guidance course cannot provide employment opportunities for students directly, the course's correct guidance and help will help students be more effective and scientific in employment [6][7]. At present, although the career guidance work of college students has been fully developed, there are still many problems [8].…”
Section: Introductionmentioning
confidence: 99%